Aji Susanto Anom's Black and White Photographic Works: A Study of Visual Psychology - Widhiyanti, Ni Wayan Widhi; Saryana, I Made (Institut Seni Indonesia Denpasar, 2024)
This study aims to map the aesthetics and emotional content implied in black and white photographic works by Aji Susanto Anom, a leading photographer from Indonesia. This research uses a visual arts approach and literature study to analyze various aspects which include techniques, compositions, themes, and messages conveyed in the works of Aji Susanto Anom. The research method used is a qualitative analysis of a number of black and white photographic works of Aji Susanto Anom that have been carefully selected. By paying attention to every visual and narrative detail, this study will identify the unique aesthetic characteristics and emotional content implicit in each work. It will also involve an understanding of the context of these works, including cultural influences, traditional values, and Aji Susanto Anom's career journey as a photographer. The results of this study are expected to provide a deeper understanding of how aesthetics and emotional content in black and white photography can be expressed through the works of Aji Susanto Anom. The findings of this study are also expected to contribute to the development of our understanding of black and white photography as a powerful artistic medium in conveying profound and inspiring messages.